Prognostic value of minimal residual disease negativity in myeloma: combined analysis of POLLUX, CASTOR, ALCYONE, and MAIA - Cavo, Michele; San-Miguel, Jesus; Usmani, Saad Z; Weisel, Katja; Dimopoulos, Meletios A; Avet-Loiseau, Hervé; Paiva, Bruno; Bahlis, Nizar J; Plesner, Torben; Hungria, Vania; Moreau, Philippe; Mateos, Maria-Victoria; et al. (Blood, 2022)
We explored minimal residual disease (MRD) in relapsed/refractory multiple myeloma (RRMM) and transplant-ineligible (TIE) newly diagnosed multiple myeloma (NDMM) using data from 4 phase 3 studies (POLLUX, CASTOR, ALCYONE, and MAIA). Each study previously demonstrated that daratumumab-based therapies improved MRD negativity rates and reduced the risk of disease progression or death by approximately half vs standards of care. We conducted a large-scale pooled analysis for associations between patients achieving complete response or better (≥CR) with MRD-negative status and progression-free survival (PFS). MRD was assessed via next-generation sequencing (10-5 sensitivity threshold). Patient-level data were pooled from all 4 studies and for patients with TIE NDMM and patients with RRMM who received ≤2 prior lines of therapy (≤2 PL). PFS was evaluated by response and MRD status. Median follow-up (months) was 54.8 for POLLUX, 50.2 for CASTOR, 40.1 for ALCYONE, and 36.4 for MAIA. Patients who achieved ≥CR and MRD negativity had improved PFS vs those who failed to reach CR or were MRD positive (TIE NDMM and RRMM hazard ratio [HR] 0.20, P < .0001; TIE NDMM and RRMM ≤2 PL HR 0.20, P < .0001). This benefit occurred irrespective of therapy or disease setting. A time-varying Cox proportional hazard model confirmed that ≥CR with MRD negativity was associated with improved PFS. Daratumumab-based treatment was associated with more patients reaching ≥CR and MRD negativity. These findings represent the first large-scale analysis with robust methodology to support ≥CR with MRD negativity as a prognostic factor for PFS in RRMM and TIE NDMM. These trials were registered at www.clinicaltrials.gov as #NCT02076009, #NCT02136134, #NCT02195479, and #NCT02252172.